May Measurement Month 2019: The Global Blood Pressure Screening Campaign of the International Society of Hypertension. Issue 2 (August 2020) - Beaney, Thomas; Schutte, Aletta E.; Stergiou, George S.; Borghi, Claudio; Burger, Dylan; Charchar, Fadi; Cro, Suzie; Diaz, Alejandro; Damasceno, Albertino; Espeche, Walter; Jose, Arun Pulikkottil; Khan, Nadia; et al.
Abstract : Elevated blood pressure remains the single biggest risk factor contributing to the global burden of disease and mortality. May Measurement Month is an annual global screening campaign aiming to improve awareness of blood pressure at the individual and population level. Adults (≥18 years) recruited through opportunistic sampling were screened at sites in 92 countries during May 2019. Ideally, 3 blood pressure readings were measured for each participant, and data on lifestyle factors and comorbidities were collected. Hypertension was defined as a systolic blood pressure ≥140 mm Hg, or a diastolic blood pressure ≥90 mm Hg (mean of the second and third readings) or taking antihypertensive medication. When necessary, multiple imputation was used to estimate participants' mean blood pressure. Mixed-effects models were used to evaluate associations between blood pressure and participant characteristics. Of 1 508 130 screenees 482 273 (32.0%) had never had a blood pressure measurement before and 513 337 (34.0%) had hypertension, of whom 58.7% were aware, and 54.7% were on antihypertensive medication. Of those on medication, 57.8% were controlled to <140/90 mm Hg, and 28.9% to <130/80 mm Hg. Of all those with hypertension, 31.7% were controlled to <140/90 mm Hg, and 350 825 (23.3%) participants had untreated or inadequately treated hypertension. Of those taking antihypertensive medication, half were taking only a single drug, and 25% reported using aspirin inappropriately. This survey is the largest ever synchronized and standardized contemporary compilation of global blood pressure data. This campaign is needed as a temporary substitute for systematic blood pressure screening in many countries worldwide. Abstract : Supplemental Digital Content is available in the text.